PENGARUH BOARD STRUCTURE DAN OWNERSHIP STRUCTURE TERHADAP MARKET CAPITALIZATION MELALUI INTELLECTUAL CAPITAL DISCLOSURE SEBAGAI VARIABEL MEDIASI - Fifi Fifi Fifi; Saarce Elsye Hatane (Business Accounting Review, 2017)
This research aimed to know the direct influence of Board structure and ownership structure on Market capitalization. In addition, this research also aimed to know the indirect affect of board structure and ownership structure on market capitalization through intellectual capital disclosure as a mediating variable. The sample used in the research consisted of 72 manufacturing companies listed on the Indonesia Stock Exchange with observation years during 2010-2015. Data processed by WarpPLS software version 5.0. The result showed that there was a positive influence of board structure on intellectual capital disclosure, negative influence of ownership structure on intellectual capital disclosure, positive influence of board structure on market capitalization, no significant influence of ownership structure on market capitalization and positive influence of intellectual capital disclosure on market capitalization. In addition, the research also found that intellectual capital disclosure successfully mediated the influence of board structure on market capitalization, and intellectual capital disclosure failed to become a mediating variable towards the influence of ownership structure to market capitalization.